Green dementia care in accommodation and care settings: a literature review. Issue 4 (5th December 2019) - Barrett, Julie; Evans, Simon; Mapes, Neil
Abstract : Purpose: The purpose of this paper is to examine the recent evidence relating to green (nature-based) dementia care for people living with dementia in long-term accommodation and care settings (housing for older people that provides both accommodation and care, such as residential care homes, nursing homes and extra care housing schemes). The review formed part of a pilot study exploring interaction with nature for people living with dementia in care homes and extra care housing schemes in the UK. Rather than a comprehensive systematic or critical literature review, the intention was to increase understanding of green dementia care to support the pilot study. Design/methodology/approach: The review draws together the published and grey literature on the impacts of green (nature-based) dementia care, the barriers and enablers and good practice in provision. People living with dementia in accommodation and care settings are the focus of this review, due to the research study of which the review is part. Evidence relating to the impacts of engaging with nature on people in general, older people and residents in accommodation and care is also briefly examined as it has a bearing on people living with dementia. Findings: Although interaction with the natural environment may not guarantee sustained wellbeing for all people living with dementia, there is some compelling evidence for a number of health and wellbeing benefits for many. However, there is a clear need for more large-scale rigorous research in this area, particularly with reference to health and wellbeing outcomes for people living with dementia in accommodation and care settings for which the evidence is limited. There is a stronger evidence base on barriers and enablers to accessing nature for people living with dementia in such settings. Research limitations/implications: The literature review was conducted to support a pilot study exploring green (nature-based) dementia care in care homes and extra care housing schemes in the UK. Consequently, the focus of the review was on green dementia care in accommodation and care settings. The study, and thus the review, also focussed on direct contact with nature (whether that occurs outdoors or indoors) rather than indirect contact (e.g. viewing nature in a photograph, on a TV screen or through a window) or simulated nature (e.g. robot pets). Therefore, this paper is not a full review of all aspects of green dementia care. Originality/value: This paper presents an up-to-date review of literature relating to green dementia care in accommodation and care settings. It was successful in increasing understanding to support a pilot study exploring opportunities, benefits, barriers and enablers to interaction with nature for people living with dementia in care homes and extra care housing schemes in the UK. It demonstrated the impacts, value and accessibility of nature engagement in these settings and identified gaps in the evidence base. This review and subsequent pilot study provide a strong platform from which to conduct future research exploring green dementia care in accommodation and care settings.